Restorative effects of Lactobacillus rhamnosus LR-32 on the gut microbiota, barrier integrity, and 5-HT metabolism in reducing feather-pecking behavior in laying hens with antibiotic-induced dysbiosis - Huang, Chenxuan; Yue, Qiaoxian; Sun, Li; Di, Keqian; Yang, Duanli; Hao, Erying; Wang, Dehe; Chen, Yifan; Shi, Lei; Zhou, Rongyan; Zhao, Guoxian; Chen, Hui (Frontiers in Microbiology, 2023)
The development of abnormal feather-pecking (FP) behavior, where laying hens display harmful pecks in conspecifics, is multifactorial and has been linked to the microbiota-gut-brain axis. Antibiotics affect the gut microbial composition, leading to gut-brain axis imbalance and behavior and physiology changes in many species. However, it is not clear whether intestinal dysbacteriosis can induce the development of damaging behavior, such as FP. The restorative effects of Lactobacillus rhamnosus LR-32 against intestinal dysbacteriosis-induced alternations need to be determined either. The current investigation aimed to induce intestinal dysbacteriosis in laying hens by supplementing their diet with the antibiotic lincomycin hydrochloride. The study revealed that antibiotic exposure resulted in decreased egg production performance and an increased tendency toward severe feather-pecking (SFP) behavior in laying hens. Moreover, intestinal and blood-brain barrier functions were impaired, and 5-HT metabolism was inhibited. However, treatment with Lactobacillus rhamnosus LR-32 following antibiotic exposure significantly alleviated the decline in egg production performance and reduced SFP behavior. Lactobacillus rhamnosus LR-32 supplementation restored the profile of the gut microbial community, and showed a strong positive effect by increasing the expression of tight junction proteins in the ileum and hypothalamus and promoting the expression of genes related to central 5-HT metabolism. The correlation analysis revealed that probiotic-enhanced bacteria were positively correlated, and probiotic-reduced bacteria were negatively correlated with tight junction-related gene expression, and 5-HT metabolism, and butyric acid levels. Overall, our findings indicate that dietary supplementation with Lactobacillus rhamnosus LR-32 can reduce antibiotic-induced FP in laying hens and is a promising treatment to improve the welfare of domestic birds.